Understanding HIV-Exposed Uninfected Children: A Narrative Review - Martina Salvi; Benedetta Fioretti; Maria Alberti; Irene Scarvaglieri; Stefania Arsuffi; Giorgio Tiecco; Francesco Castelli; Eugenia Quiros-Roldan (Viruses)
The widespread implementation of antiretroviral therapy has significantly reduced HIV-related mortality and mother-to-child transmission. Despite being HIV-uninfected, HIV-exposed children (HEU) seem to face heightened risks of immune dysfunction, cardiometabolic diseases, growth delays, reduction in bone mineral density, and neurocognitive impairments compared to HIV-unexposed uninfected peers. These vulnerabilities can be attributed to maternal immune dysregulation during pregnancy, antiretroviral (ART) toxicity, HIV exposure, and adverse socioeconomic and nutritional environments. Emerging evidence highlights the impact of antiviral therapy exposure, particularly tenofovir disoproxil fumarate, on HEU mitochondrial dysfunction, bone resorption, neurocognitive delays, and zidovudine on cardiac abnormalities. This narrative review explores the multisystem effects of ART exposure in HEU children, focusing on immune function, neurodevelopment, cardiovascular health, growth, and bone metabolism. By synthesizing findings from diverse studies, the review aims to provide a comprehensive understanding of the potential risks associated with ART regimens and identify future research priorities to improve outcomes for HEU children.